1996
DOI: 10.1530/eje.0.1340398
|View full text |Cite
|
Sign up to set email alerts
|

Aminoguanidine and diabetic neuropathy

Abstract: In this issue, Miyauchi and colleagues (1) present a study in which they have administered aminoguanidine orally for 16 weeks to young rats with streptozotocininduced diabetes. Whereas motor nerve conduction velocity (MNCV) kept increasing with time in the nondiabetic control rats and reached a plateau at 16 weeks, initially no such increase was noted in diabetic rats on aminoguanidine. However, after 2 months of treatment a dose-dependent progressive increase in MNCV was noted, which, at the dose of 50 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…As has been previously reported, we demonstrate that treating streptozotocin-induced diabetic rats with sorbinil or aminoguanidine significantly improves the reduction in EBF and slowing of MNCV [3][4][5][6][7][8][9][10][11][12][24][25][26][27][28]. In sorbinil treated diabetic rats EBF and MNCV remained suppressed by 15 and 18%, respectively compared to controls, whereas in aminoguanidine treated rats EBF and MNCV, compared to controls, was decreased by 6 and 16%, respectively.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…As has been previously reported, we demonstrate that treating streptozotocin-induced diabetic rats with sorbinil or aminoguanidine significantly improves the reduction in EBF and slowing of MNCV [3][4][5][6][7][8][9][10][11][12][24][25][26][27][28]. In sorbinil treated diabetic rats EBF and MNCV remained suppressed by 15 and 18%, respectively compared to controls, whereas in aminoguanidine treated rats EBF and MNCV, compared to controls, was decreased by 6 and 16%, respectively.…”
Section: Discussionsupporting
confidence: 72%
“…We have previously shown that endothelialdependent vascular relaxation of arterioles that provide circulation to the region of the sciatic nerve is impaired by diabetes [35,36]. In the present study we sought to determine the effect treatment of diabetic rats with sorbinil, an aldose reductase inhibitor, aminoguanidine, an inhibitor of nonenzymatic glycation, or myoinositol supplementation has on EBF, MNCV as well as vascular relaxation of arterioles that provide circulation to the region of the sciatic nerve.As has been previously reported, we demonstrate that treating streptozotocin-induced diabetic rats with sorbinil or aminoguanidine significantly improves the reduction in EBF and slowing of MNCV [3][4][5][6][7][8][9][10][11][12][24][25][26][27][28]. In sorbinil treated diabetic rats EBF and MNCV remained suppressed by 15 and 18%, respectively compared to controls, whereas in aminoguanidine treated rats EBF and MNCV, compared to controls, was decreased by 6 and 16%, respectively.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…Functional and structural assessment of the impact of glycation on nerve has been hampered by the lack of molecules, analogous to ARIs, which specifically inhibit glycation reactions. In this context, aminoguanidine has been used, but it clearly has several other pharmacological properties ( Monnier, 1996 ) , and its use as an investigative tool is flawed. New glycation inhibitors, such as pyridoxamine, might offer new insight into the effects of macromolecule glycation in nerve dysfunction ( Metz et al, 2003 ) .…”
Section: Introductionmentioning
confidence: 99%